Communication via social media as an educational technology of nursing assistance to clients submitted to high digestive endoscopy (Research, Society and Development, 2021)
This study had as objectives: To identify if the information sent by social media were assimilated by the clients who will be submitted to Upper Digestive Endoscopy; describe the conditions of preparation of the patient for the performance of Upper Digestive Endoscopy when receiving information via social media and analyze the impact of communication via social media as an educational technology according to the King's Goal Achievement Theory. Method: Convergent Care Research, carried out in a federal hospital in Rio de Janeiro, with 17 clients undergoing pre-examination of Upper Digestive Endoscopy. A semi-structured interview was used, followed by a dialogue with each participant. Thematic analysis applied. Results: A significant adherence of the patient to the preparation for the exam was observed after receiving the information, both in telephone contact and in the message via Whatsapp®, the interaction between nurse / patient was observed throughout the process, corroborating King's theory when says that individuals involved in an interaction bring different ideas as well as individual attitudes and perceptions to be exchanged. Conclusion: It became evident that, when rethinking our practice, in addition to sharing our knowledge, we also assumed responsibility for our action, with the user of our service and his companion. The nurse is in a position to assess what people know about their health and how they act to maintain it. Through the process of human interaction, it equates its scientific knowledge with the SELF of the client (person, family or community) in order to, through communication, set the goals and the means to achieve the objectives.